ANALISIS PENGARUH HUMAN CREATIVITY PADA KONSULTAN PAJAK DALAM KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG: FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Hendra Prasetya; Nurul Azizah (Media Bina Ilmiah, 2023)
There are many factors that influence smartphone purchasing decisions, including: product quality, brand image and brand trust. This is what you want to know from this research. The variables studied are product quality, brand image and brand trust as independent variables and purchase decisions as the dependent variable. The population is students of the Faculty of Economics and Business, Wijaya Kusuma University, Surabaya, while the determination of the sample using purposive sampling. The sample studied was 100 respondents. Data were analyzed by multiple linear regression and the hypothesis was tested by t test. The results of each of the independent variables studied are product quality, brand image and brand trust have a positive and significant effect on Samsung smartphone purchasing decisions among students of the Faculty of Economics and Business, Wijaya Kusuma University, Surabaya. Samsung smartphone manufacturers should continue to improve the quality of their products through product innovation, improve brand image and brand trust among consumers